Thalictrum semiscandens (Ranunculaceae), almost totally overlooked since its publication, is merged with T. trichopus - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2020)
Thalictrum semiscandens (Ranunculaceae) was described from Lushui County in northwestern Yunnan, China and has been almost totally overlooked since its publication. Based on a critical examination on herbarium specimens (including type material), we demonstrate that it is conspecific with T. trichopus, a species widely distributed in southwestern China (Sichuan and Yunnan). We therefore reduce T. semiscandens to the synonymy of T. trichopus herein. Lectotypification is proposed for T. trichopus.